2006
DOI: 10.1021/om050812+
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study on the Regioselectivity of Styrene Polymerization with an ansa-Metallocene Catalyst

Abstract: The mechanism of regioselectivity of styrene polymerization with a Cp-based ansa-matallocene catalyst (Cp = η5-C5H5) was investigated using density functional theory (DFT). The metallocene catalyst studied in this work, (CH3)2SiCp2Ti(CH3)2, is known to produce polystyrene via the secondary insertion of styrene. A cationic species, SiH2Cp2Ti+−CH3, is used as an activated form of the catalyst for modeling the initiation of styrene polymerization. The results show that primary insertion is more favorable than sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…[15] This is consistent with DFT studies for titanocene catalysts which showed that primary insertion is favored in the initiation step but leads to a stable product that blocks additional primary insertions, thus favoring secondary insertion in the propagation step. [16,17] In order to get a better insight in these reactivity and mechanistic issues, we have undertaken a DFT study of the initiation process of styrene polymerization promoted by our neodymocene complexes. The influence of the nature of the bridge in the ancillary Cp'XMe 2 Flu' ligand (CMe 2 vs. SiMe 2 ) and of the "active" (allyl vs. alkyl) group has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[15] This is consistent with DFT studies for titanocene catalysts which showed that primary insertion is favored in the initiation step but leads to a stable product that blocks additional primary insertions, thus favoring secondary insertion in the propagation step. [16,17] In order to get a better insight in these reactivity and mechanistic issues, we have undertaken a DFT study of the initiation process of styrene polymerization promoted by our neodymocene complexes. The influence of the nature of the bridge in the ancillary Cp'XMe 2 Flu' ligand (CMe 2 vs. SiMe 2 ) and of the "active" (allyl vs. alkyl) group has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, many computational studies have been reported to understand the mechanisms of transition metal‐catalyzed olefin polymeriza‐tions . Karttunen et al studied the influences of the ligands on hafnocene‐catalyzed polymerization computationally, and found that steric effects of the ligand affect the activation energy in chain propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Karttunen et al studied the influences of the ligands on hafnocene‐catalyzed polymerization computationally, and found that steric effects of the ligand affect the activation energy in chain propagation. Yang et al's DFT study of Ti‐catalyzed copolymerization of ethylene and styrene indicated that styrene prefers 1,2‐insertion to 2,1‐insertion initially, but the subsequent styrene insertion is dominated by 2,1‐insertion mode. The QM/MM study of Kang et al on the 1‐hexene polymerization catalyzed by a dicationic rare earth metal catalyst found that 1‐hexene polymerization prefers 1,2‐insertion to 2,1‐insertion.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Ziegler-Natta catalysts have been extensively studied both experimentally [3] and theoretically [4], only few studies have been dealt with copolymerization of CGCs [5,6]. Theoretical studies on copolymerization can give an insight into the mechanism of monomer insertion, including the structure of transition state, activation energy and origin of regioselectivity.…”
Section: Introductionmentioning
confidence: 99%